Houseplant, indoor air pollution, and cardiovascular effects among elderly subjects in Taipei, Taiwan - Chen, Ruey-Yu; Ho, Kin-Fai; Hong, Gui-Bing; Chuang, Kai-Jen (The Science of the total environment, 2020)
Previous studies have documented the linkage between houseplant usage and indoor air quality (IAQ) improvement. However, the effect of houseplant on the association between indoor air quality and cardiovascular health is still unknown. We recruited 100 elderly subjects from 100 houses with (50) or without houseplants (50) in Taipei and conducted six 24-hour house visits for each elderly subject between 2015 and 2016. The particulate matter less than or equal to 2.5 μm in diameter (PM2.5), total volatile compounds (TVOCs), heart rate (HR) and blood pressure (BP) were continuously measured in each house visit. The association between indoor air pollution, BP and HR was investigated by mixed-effects. We found that the elderly subjects in houses without houseplants were exposed to higher indoor PM2.5 and TVOCs levels compared to the elderly subjects' exposures in houses with houseplants. Also, the elderly subjects' HR, systolic BP (SBP) and diastolic BP (DBP) were higher in houses without houseplants than those in houses with houseplants. Moreover, high indoor air pollution levels were associated with elevated BP and HR, especially among subjects in houses without houseplants. Accordingly, we concluded that indoor air pollution was associated with cardiovascular effects. Houseplant could improve IAQ and cardiovascular health among elderly subjects in Taipei, Taiwan. [Display omitted] •Indoor PM2.5 and TVOCs are associated with adverse cardiovascular effects.•Houseplants are associated with indoor air quality and cardiovascular health.•Houseplants can reduce indoor PM2.5 and TVOCs levels.